Bis(1-ammonioethane-1,1-diyldiphosphonato-κ2O,O′)diaquacobalt(II) nonahydrate - Vladimir V. Bon; Anatolij V. Dudko; Alexandra N. Kozachkova; Vasily I. Pekhnyo; Natalia V. Tsaryk (Acta Crystallographica Section E, 2010)
In the title compound, [Co(C2H8NO6P2)2(H2O)2]·9H2O, the CoII atom has a slightly distorted octahedral coordination environment consisting of four deprotonated phosphonate O atoms of two independent 1-aminoethylidendiphosphonate anions and complemented by the O atoms of two water molecules in cis positions. The anions exists in the zwitterionic form (protonated amino group and two deprotonated phosphonate O atoms) and constitute two six-membered chelate rings. The crystal structure also contains nine partly disordered uncoordinated water molecules, which create an extensive three-dimensional network of strong O—H...O and N—H...O hydrogen bonds.